Synovial Fluid Changes in Induced Infectious Arthritis in Calves - Francoz, David (J Vet Intern Med, 2008)
The objective was to develop an experimental model of septic arthritis in calves and to evaluate the effect of treatment on cytologic and bacteriologic variables of synovial fluid. The right tarsus of 7 healthy Holstein bull calves were inoculated with 10(8) colony‐forming units of viable Escherichia coli of a pap‐positive strain (day 1). On day 2, joint lavage was performed and antibiotic treatment was instituted. Cytologic examinations, bacterial cultures, and pap factor determinations by polymerase chain reaction (PCR) were performed on synovial fluid samples that were collected daily until day 4, then every 4 days until day 24. Results of physical examination, the severity of lameness, and swelling were recorded. Clinical signs of septic arthritis appeared on day 2 and persisted until day 9 for all calves. Bacterial cultures from all calves were positive for E coli on day 2, and remained positive until day 3 for 1 calf and until day 4 for 5 calves. In addition, PCR results were positive for all calves, with 6 positive through day 3 and 1 positive through day 4, after which a positive result was again obtained on day 24. Synovial fluid neutrophil counts and white blood cell counts were significantly increased on days 2–4; however, synovial total protein concentrations were increased (P < .05) throughout the experiment in comparison to day 1. Results of all bacterial cultures were negative on day 8, although clinicopathologic signs of inflammation persisted until day 20. This model successfully induced acute septic arthritis in calves. Rapid recovery occurred within 1 week when an appropriate treatment was instituted early in the course of the disease